Theoretical Study of the Motion Characteristics of a Variable Length Connecting Rod Mechanism - CHEN, Jiadui; LIU, Qinghua; YANG, Kai (Engineering Transactions, 2022)
The sustainable development of society calls for automobile engines with high efficiency and very low pollutant emission. The variable compression ratio (VCR) technique is one of the effective methods to deal with this issue. Engines with variable length connecting rod (VLEs) yield higher efficiency than other VCR engines. This paper focuses on a variable length connecting rod mechanism that achieves a VCR by changing the positions of the bottom dead center (BDC) and the top dead center (TDC) (controlled by the rotation of the eccentric sleeve) relative to the crankshaft. A kinematic model is also proposed to calculate and analyze the motion characteristics of the variable length connecting rod mechanism. The effects of eccentric size and eccentric phase on the piston motion, the TDC and BDC positions, the stroke length, the crank angles at TDC and BDC, and the compression ratio are studied in detail. It is found that the piston exhibits good motion characteristics with proper eccentric size and eccentric phase, and the compression ratio can be adjusted by varying the eccentric phase with proper eccentric size. A comparison between the proposed mechanism with another mechanism is also conducted. Therefore, this work can serve as a necessary reference for designing, analyzing, and optimizing VLEs.